Afritoxinones A and B, dihydrofuropyran-2-ones produced by Diplodia africana the causal agent of branch dieback on Juniperus phoenicea - Evidente, Antonio; Masi, Marco; Linaldeddu, Benedetto T.; Franceschini, Antonio; Scanu, Bruno; Cimmino, Alessio; Andolfi, Anna; Motta, Andrea; Maddau, Lucia (PHYTOCHEMISTRY, 2012)
Two phytotoxic dihydrofuropyran-2-ones, named afritoxinones A and B. were isolated from liquid culture of Diplodia africana. a fungal pathogen responsible for branch dieback of Phoenicean juniper in Italy. Additionally, six others known metabolites were isolated and characterized: oxysporone, sphaeropsidin A, epi-sphaeropsidone, R-(-)-mellein, (3R,4R)-4-hydroxymellein and (3R,4S)-4-hydroxymellein. The structures of afritoxinones A and B were established by spectroscopic and optical methods and determined to be as (3aS{*},6R{*}-,7aS)-6-methoxy-3a,7a-dihydro-3H,6H-furo\{[\}2,3-b]pyran-2-o ne and (3aR{*},6R{*},7aS)-6-methoxy-3a,7a-dihydro-3H,6H-furo\{[\}2,3-b]pyran-2-on e, respectively. The phytotoxic activity of afritoxinones A and B and oxysporone was evaluated on host (Phoenicean juniper) and non-host plant (holm oak, cork oak and tomato) by cutting and leaf puncture assay. Oxysporone proved to be the most phytotoxic compound. This study represents the first report of secondary metabolites produced by D. africana. In addition, the taxonomic implications of secondary metabolites in Botryosphaeriaceae family studies are discussed. (C) 2012 Elsevier Ltd. All rights reserved.
The following values have no corresponding Zotero field: pub-location: THE BOULEVARD, LANGFORD LANE, KIDLINGTON, OXFORD OX5 1GB, ENGLAND publisher: PERGAMON-ELSEVIER SCIENCE LTD
Keywords: Afritoxinones A and B; Botryosphaeriaceae; Diplodia africana; Juniperus phoenicea; Phytotoxins

Diplopyrone, a New Phytotoxic Tetrahydropyranpyran-2-one Produced by Diplodia mutila, a Fungus Pathogen of Cork Oak - Evidente, Antonio; Maddau, Lucia; Spanu, Emanuela; Franceschini, Antonio; Lazzaroni, Silvia; Motta, Andrea (Journal of Natural Products, 2003)
A new phytotoxic monosubstituted tetrahydropyranpyran-2-one, named diplopyrone (1), was isolated from the liquid culture filtrates of Diplodia mutila, a plant pathogenic fungus causing a form of canker disease of cork oak (Quercus suber). Diplopyrone was characterized, using spectroscopic and chemical methods, as 6-[(1S)-1-hydroxyethyl]-2,4a,6,8a-tetrahydropyran[3,2-b]pyran-2-one. The absolute stereochemistry of the chiral secondary hydroxylated carbon (C-9), determined by application of Mosher's method, proved to be S. Diplopyrone assayed at a 0.01?0.1 mg/mL concentration range caused necrosis and wilting on cork oak cuttings. On a nonhost plant, tomato, diplopyrone caused brown discoloration or stewing on the stem.
Keywords: Phytopathogenic fungi; Phytotoxins; relative and/or absolute configuration; structure–activity relationships

Diplopyrone, a New Phytotoxic Tetrahydropyranpyran-2-one Produced by Diplodia mutila, a Fungus Pathogen of Cork Oak - Evidente, Antonio; Maddau, Lucia; Spanu, Emanuela; Franceschini, Antonio; Lazzaroni, Silvia; Motta, Andrea (Journal of Natural Products, 2003)
A new phytotoxic monosubstituted tetrahydropyranpyran-2-one, named diplopyrone (1), was isolated from the liquid culture filtrates of Diplodia mutila, a plant pathogenic fungus causing a form of canker disease of cork oak (Quercus suber). Diplopyrone was characterized, using spectroscopic and chemical methods, as 6-[(1S)-1-hydroxyethyl]-2,4a,6,8a-tetrahydropyran[3,2-b]pyran-2-one. The absolute stereochemistry of the chiral secondary hydroxylated carbon (C-9), determined by application of Mosher's method, proved to be S. Diplopyrone assayed at a 0.01?0.1 mg/mL concentration range caused necrosis and wilting on cork oak cuttings. On a nonhost plant, tomato, diplopyrone caused brown discoloration or stewing on the stem.
The following values have no corresponding Zotero field: publisher: American Chemical Society accession-num: 12608876
Keywords: Phytopathogenic fungi; Phytotoxins; relative and/or absolute configuration; structure–activity relationships